Identification of genes related to sexual differentiation and sterility in embryonic gonads of Mule ducks by transcriptome analysis - Yang, Yu; Li, Xuelian; Ye, Shengqiang; Chen, Xing; Wang, Lixia; Qian, Yunguo; Xin, Qingwu; Li, Li; Gong, Ping (Frontiers in Genetics, 2022)
The key genes of avian gonadal development are of great significance for sex determination. Transcriptome sequencing analysis of Mule duck gonad as potential sterile model is expected to screen candidate genes related to avian gonad development. In this study, the embryonic gonadal tissues of Mule ducks, Jinding ducks, and Muscovy ducks were collected and identified. Six sample groups including female Mule duck (A), male Mule duck (B), female Jinding duck (C), male Jinding duck (D), female Muscovy duck (E), and male Muscovy duck (F) were subjected to RNA sequencing analysis. A total of 9,471 differential genes (DEGs) and 691 protein-protein interaction pairs were obtained. Totally, 12 genes (Dmrt1, Amh, Sox9, Tex14, Trim71, Slc26a8, Spam1, Tdrp, Tsga10, Boc, Cxcl14, and Hsd17b3) were identified to be specifically related to duck testicular development, and 11 genes (Hsd17b1, Cyp19a1, Cyp17a1, Hhipl2, Tdrp, Uts2r, Cdon, Axin2, Nxph1, Brinp2, and Brinp3) were specifically related to duck ovarian development. Seven genes (Stra8, Dmc1, Terb1, Tex14, Tsga10, Spam1, and Plcd4) were screened to be specifically involved in the female sterility of Mule ducks; eight genes (Gtsf1, Nalcn, Tat, Slc26a8, Kmo, Plcd4, Aldh4a1, and Hgd) were specifically involved in male sterility; and five genes (Terb1, Stra8, Tex14 Tsga10 and Spam1) were involved in both female and male sterility. This study provides an insight into the differential development between male and female gonads of ducks and the sterility mechanism of Mule ducks through function, pathway, and protein interaction analyses. Our findings provide theoretical basis for the further research on sex determination and differentiation of birds and the sterility of Mule ducks.